2011
DOI: 10.1007/s10404-011-0896-0
|View full text |Cite
|
Sign up to set email alerts
|

Integrated optofluidic microsystem based on vertical high-order one-dimensional silicon photonic crystals

Abstract: In this work, fabrication and testing of an optofluidic microsystem exploiting high aspect-ratio, vertical, silicon/air one-dimensional (1D) photonic crystals (PhC) are reported. The microsystem is composed of an electrochemically micromachined silicon substrate integrating a 1D PhC featuring high-order bandgaps in the near-infrared region, bonded to a glass cover provided with inlet/outlet holes for liquid injection/extraction in/out the PhC-itself. Wavelength shifts of the reflectivity spectrum of the photon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Optical read-out is undoubtedly a very fascinating solution among detection methods, as it allows remote sensing of the investigated parameters, being thus minimally invasive, while miniaturization enables testing with ultra-low quantities of materials, both important factors particularly in the fields of biological, biochemical and biomedical analyses [2]. Various types of sensors that respond to the mentioned requirements have been lately investigated, based on resonant micro-cavities [1,3,4], photonics crystals [5][6][7][8][9], ring resonators [10][11][12][13][14][15], or whispering gallery modes [16], just to cite a few of them. However, there is still the need of demonstrating the functionality of simple and low-cost devices to be used as core elements of micro-opto-fluidic sensors combined with suitable readout methods.…”
Section: Introductionmentioning
confidence: 99%
“…Optical read-out is undoubtedly a very fascinating solution among detection methods, as it allows remote sensing of the investigated parameters, being thus minimally invasive, while miniaturization enables testing with ultra-low quantities of materials, both important factors particularly in the fields of biological, biochemical and biomedical analyses [2]. Various types of sensors that respond to the mentioned requirements have been lately investigated, based on resonant micro-cavities [1,3,4], photonics crystals [5][6][7][8][9], ring resonators [10][11][12][13][14][15], or whispering gallery modes [16], just to cite a few of them. However, there is still the need of demonstrating the functionality of simple and low-cost devices to be used as core elements of micro-opto-fluidic sensors combined with suitable readout methods.…”
Section: Introductionmentioning
confidence: 99%
“…One of these challenges is to create accurate, simple and cheap sensors. Several possible sensor conceptions were suggested [104,105] although they are not really suitable for widespread usage because of their complexity, difficult fabrication processes, and so on. A solution to overcome such a problem might be a usage of an opto-fluidic sensor with a specifically designed microlens array as its main component ( Fig.…”
Section: Opto-fluidicsmentioning
confidence: 99%
“…In this perspective, we developed three-dimensional silicon microstructures (3D-SMSs) formed by periodic arrays of parallel ≈3 m-thick silicon walls separated by ≈5 m-wide, 50 m-deep air gaps [5,6]. We demonstrated that these microdevices are suitable for the culture of human cancer cells [7,8] in 3D with a proliferation rate similar to the 2D counterpart.…”
Section: Introductionmentioning
confidence: 99%